Foliar application of putricine enhances salt stress tolerance in sunflower (Helianthus annuus) - Gul, Humaira; Rauf, Mamoona; Khushnood ur Rehman; Khan, Yaseen; Yaseen, Tabassum; Akbar, Kamran; Noreen, Salma; Ishfaq, Muhmmad (Journal of Pure and Applied Agriculture, 2023)
The occurrence of salt in soil and water is the most vital and serious problem in agricultural land which hampers crop productivity all over the world. There are different techniques to beat the salt-forced impact on the development of the plant and its yield. This project was designed to observe the ameliorative role of exogenously applied putricine concerning growth, yield, and biochemical parameters of Helianthus annuus grown under salinity stress. The experiment was a completely randomized blocked design and plants were irrigated with different concentrations of salt (50mM, 100mM, and 150mM) as well as foliarly applied with different doses of putricine (0.1 mM, 1 mM, and 2 mM). Observations of the current study revealed, a significant reduction in different growth parameters (Root length, shoot length, fresh and dry biomass, number of leaves, seed weight, and seed number per plant), different biochemical aspects (IAA content, photosynthetic pigments, nonreducing sugars, total carbohydrates, and total proteins). Under the same environment, secondary metabolites (Phenols, lycopene, beta carotene, terpenoids, and total antioxidants) increased under stressed conditions. Foliarly applied putricine induced stimulatory effect and improved above mentioned parameters under normal and stressed conditions. Results of the current investigation suggested, that foliar application of putricine may have a protective role for Helianthus annuus and create a perspective for increasing tolerance in this plant for salinity stress. It is recommended that putricine application @ 2 mM is considered as the best dose for sunflower growth and better yield under a normal and stressed environment. © 2021 Department of Agricultural Sciences, AIOU